The Effect of Time Management on Learning Achievement of Students Jagad 'Alimussirry - Sholaita, Sholaita (Journal Intellectual Sufism Research (JISR), 2019)
Function education in the view of Islam is not much different with the goal of national education, where education serves to improve the competency of an individual as a learner. There are two factors that influence the learning outcomes of an individual, the first is internal factors and the second is external factors. The purpose of this study was to determine the effect of time management on the achievement of students learning Islamic boarding school Jagad 'Alimussirry. The research method carried out in this study is the statistical method . The instrument test technique in this study was to test the validity and reliability while the data analysis technique used the linearity test. Hypothesis testing uses Partial Test (T Test), coefficient of determination and simple linear regression analysis. The results obtained in the research that have been carried out without going through or using treatment that can be applied in the form of time management training, the results of statistical testing using simple linear regression analysis techniques can be stated that time management does not significantly influence students achievement in Jagad ‘Alimussirry Islamic boarding school.